Language Units Expressing the Notion of Degree or Quantity on Turkic Monuments - Yerlan Kassenov, Zauresh Akhmetzhanova, Yermukhamet Maralbek,; Kerembekova, Marzhan (Opción, 2019)
The aim of the study is to investigate the language units expressing the notion of degree or quantity on Old Turkic monuments via comparative qualitative research methods. As a result, formation and transferral methods for the notion of quantity are clearly rooted in three linguistic levels: phonetics, lexicon, and grammar. In conclusion, the category of measure even in the Old Turkic period, a foundational historical period in the development of the Kazakh language, has reached the level of a general language category with its lexical and grammatical forms and methods fully formed.